Preparation method of high-purity lithium carbonate with bimodal particle size distribution

CN122897425APending Publication Date: 2026-10-13YIFENG SHIDAI NEW ENERGY MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113200.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-26
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004](1)粒径分布单一,难以兼顾高压实密度与高倍率性能

Benefits of technology

[0020](1)该制备方法制备的碳酸锂,其纯度能够达到99.9%以上,产品纯度显著提高;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897425A_ABST
    Figure CN122897425A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of high-purity lithium carbonate with a bimodal particle size distribution. A saturated lithium carbonate solution is used as a bottom liquid, and the bottom liquid is heated to 90-95 DEG C, and lithium carbonate seeds are added. A carbonated lithium bicarbonate solution is added to the bottom liquid in a dropwise manner, and ultrasonic treatment is started in the process of feeding 1 / 6-1 / 3 of the volume of the lithium bicarbonate solution, and the ultrasonic treatment is stopped in the process of feeding the remaining material. After the feeding is completed, stirring reaction, solid-liquid separation, washing and drying are carried out to obtain the high-purity lithium carbonate with the bimodal particle size distribution. The purity of the lithium carbonate prepared by the preparation method can reach more than 99.9%, and the product purity is significantly improved. The product has a bimodal particle size, and the tap density of the product can reach 1.20 g / cm3 or more. The crystal presents a rod-like morphology, and the generation of abnormal morphologies such as needle-like and flaky morphologies which are not conducive to compact packing is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-purity lithium carbonate preparation technology, and particularly relates to a method for preparing high-purity lithium carbonate with a bimodal particle size distribution. Background Technology

[0002] Lithium carbonate is a key lithium source for cathode materials in lithium-ion batteries (such as lithium iron phosphate and lithium nickel cobalt manganese oxide). Its purity, particle size distribution, and morphology directly affect the compaction density, rate performance, and cycle life of the cathode material. With the rapid development of new energy vehicles and energy storage industries, the market demand for high-purity lithium carbonate is increasing, while higher requirements are being placed on the particle size distribution and morphology of lithium carbonate products.

[0003] The carbonization pyrolysis method is one of the mainstream processes for preparing high-purity lithium carbonate. Its principle involves carbonizing industrial-grade or battery-grade lithium carbonate to obtain a soluble lithium bicarbonate solution, which is then pyrolyzed to yield high-purity lithium carbonate. However, existing carbonization pyrolysis processes for preparing lithium carbonate products have the following technical problems:

[0004] (1) Uniform particle size distribution makes it difficult to achieve both high compaction density and high rate performance. When lithium carbonate with a uniform particle size distribution is sintered as cathode material, gaps remain between large particles, while small particles have a low packing density, making it impossible to achieve the densest packing. Existing technologies usually complete crystallization in one step during pyrolysis, making it difficult to precisely control the particle size distribution.

[0005] (2) The morphology is uncontrollable, which affects the processing performance of the cathode material. The pyrolysis products of ordinary lithium carbonate are mostly needle-shaped or plate-shaped, which affects the dense packing.

[0006] (3) Product purity is difficult to further improve. In the existing carbonization pyrolysis process, lithium carbonate easily releases residual impurity ions (such as Na+) in the solution during rapid pyrolysis. + K + Ca 2+ Mg 2+ SO4 2- Impurity ions (such as impurities) can be trapped inside the crystal, making it difficult to achieve higher purity standards (such as above 99.9%). This is because the seed crystals generated under conventional pyrolysis conditions have a large particle size and limited specific surface area, making it easy for impurity ions to be captured by the growth interface and trapped inside the crystal lattice during crystal growth.

[0007] (4) Scale buildup is likely to occur on the reactor walls during pyrolysis, leading to lithium loss and difficulties in equipment cleaning. Lithium carbonate generated during the pyrolysis of lithium bicarbonate solution easily adheres to the reactor walls, forming scale. This not only causes lithium loss but also affects heat transfer efficiency and reduces product yield. Conventional mechanical scraping or chemical cleaning methods have limited effectiveness and increase operating costs.

[0008] Therefore, there is an urgent need to develop a method for preparing high-purity lithium carbonate that can simultaneously control the particle size distribution, crystal morphology, and purity of lithium carbonate, while overcoming the problem of thermal decomposition and wall formation. Summary of the Invention

[0009] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing high-purity lithium carbonate that simultaneously controls the particle size distribution, crystal morphology and purity of lithium carbonate, while overcoming the problem of thermal decomposition and wall formation.

[0010] Technical solution: The present invention provides a method for preparing high-purity lithium carbonate with a bimodal particle size distribution, comprising the following steps:

[0011] (1) Using a saturated lithium carbonate solution as the base liquid, heat it to 90-95℃ and add lithium carbonate seed crystals;

[0012] (2) Add the carbonized lithium bicarbonate solution to the bottom liquid in step (1) by dripping. During the first 1 / 6-1 / 3 of the feeding volume of the lithium bicarbonate solution, turn on the ultrasonic treatment. During the feeding of the remaining material, turn off the ultrasonic treatment. After the feeding is completed, stir the reaction, separate the solid and liquid, wash and dry to obtain high-purity lithium carbonate with bimodal particle size distribution.

[0013] Furthermore, the volume ratio of lithium bicarbonate solution to saturated lithium carbonate solution used in this preparation method is (10-25):1.

[0014] Furthermore, in step (1) of the preparation method, the amount of lithium carbonate seed crystals added is 2%-10% of the mass of lithium carbonate in the lithium bicarbonate solution.

[0015] Furthermore, in step (2) of the preparation method, the dropping rate is 50-100 mL / min.

[0016] Furthermore, in step (2) of the preparation method, the ultrasonic frequency of the ultrasonic treatment is 24-40kHz and the ultrasonic power is 200-500W.

[0017] Furthermore, in step (2) of the preparation method, the stirring reaction time is 30-150 min and the stirring rate is 200-500 rpm.

[0018] Furthermore, in step (2) of the preparation method, the drying is performed under vacuum at 100-120°C for 4-8 hours.

[0019] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are:

[0020] (1) The lithium carbonate prepared by this method has a purity of over 99.9%, and the product purity is significantly improved;

[0021] (2) The lithium carbonate prepared by this method has a bimodal particle size and the tap density of the product can reach 1.19 g / cm³ or higher;

[0022] (3) The lithium carbonate prepared by this method has a rod-shaped crystal, which avoids the formation of abnormal morphologies such as needle-shaped and plate-shaped crystals that are not conducive to dense packing.

[0023] (4) The preparation method is simple to operate, has good reproducibility, and is easy to scale up industrially. Attached Figure Description

[0024] Figure 1 This is a SEM image of the lithium carbonate prepared in Example 1 of the present invention;

[0025] Figure 2 This is a particle size distribution diagram of lithium carbonate prepared in Example 1 of the present invention;

[0026] Figure 3 This is a particle size distribution diagram of lithium carbonate prepared in Example 2 of the present invention;

[0027] Figure 4 The particle size distribution diagram of lithium carbonate prepared in Example 3 of this invention is shown.

[0028] Figure 5 This is a particle size distribution diagram of lithium carbonate prepared in Comparative Example 1 of the present invention;

[0029] Figure 6 This is a particle size distribution diagram of lithium carbonate prepared in Comparative Example 2 of the present invention;

[0030] Figure 7 This is a particle size distribution diagram of lithium carbonate prepared in Comparative Example 3 of the present invention;

[0031] Figure 8 This is a SEM image of the lithium carbonate prepared in Comparative Example 4 of the present invention.

[0032] Figure 9 This is a particle size distribution diagram of lithium carbonate prepared in Comparative Example 4 of the present invention. Detailed Implementation

[0033] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0034] The raw material used in the following embodiments and comparative examples of the present invention is battery-grade lithium carbonate, the purity of which is shown in Table 1 below.

[0035] Table 1 Purity of Battery-Grade Lithium Carbonate

[0036]

[0037] The steps for carbonizing battery-grade lithium carbonate described above are as follows:

[0038] (1) Battery-grade lithium carbonate and pure water are mixed at a solid-liquid ratio of 1:25 and stirred evenly to form a lithium carbonate slurry, which is then transported to the carbonation reactor.

[0039] (2) Turn on the microbubble generator and introduce high-purity carbon dioxide gas into the slurry in the form of microbubbles. Carry out the carbonization reaction under normal temperature (20-30℃) and normal pressure conditions. During the carbonization process, lithium carbonate reacts with water and carbon dioxide to generate soluble lithium bicarbonate. The carbonization reaction time is 2-3 hours. After the carbonization reaction is completed, stop introducing carbon dioxide, filter the carbonized liquid to remove insoluble impurities, and obtain a refined lithium bicarbonate solution.

[0040] The composition of the lithium bicarbonate solution formed by carbonization is shown in Table 2 below.

[0041] Table 2 Composition of different batches of carbonized liquid

[0042]

[0043] Furthermore, the particle size D50 of the lithium carbonate seeds involved in the following embodiments and comparative examples of the present invention is 5-10 μm.

[0044] Example 1

[0045] The method for preparing lithium carbonate in Example 1 includes the following steps:

[0046] (1) Add 2 L of saturated lithium carbonate solution to the reactor, heat to 90°C, add lithium carbonate seed crystals, the amount of which is 5% of the mass of lithium carbonate in the lithium bicarbonate solution, and stir evenly.

[0047] (2) Take a total volume of 30 L of lithium bicarbonate solution and add it continuously to the reactor using a peristaltic pump at a dropping rate of 100 mL / min.

[0048] (3) During the first 10 L feeding process (i.e. the first 1 / 3 material feeding stage), ultrasonic treatment is turned on with an ultrasonic frequency of 28 kHz and a power of 350 W; during the remaining 20 L feeding process, ultrasonic treatment is turned off.

[0049] (4) After the addition is complete, continue stirring at a stirring rate of 300 rpm for 60 min. Then, the reaction slurry is separated into solid and liquid. The filter cake is washed twice with high-temperature pure water and dried under vacuum at 110°C for 6 h to obtain lithium carbonate product.

[0050] Product testing: The lithium carbonate product was measured using a laser particle size analyzer, and the particle sizes were D10 = 2.648 μm, D50 = 11.013 μm, and D90 = 23.157 μm. ICP-OES analysis showed the results, as shown in Table 3, with a purity of 99.994%. It should be noted that the ICP-OES analysis was performed on lithium carbonate; therefore, XRD characterization was not performed on this product.

[0051] Table 3. Composition content of lithium carbonate product prepared in Example 1

[0052]

[0053] Example 2

[0054] The method for preparing lithium carbonate in Example 2 includes the following steps:

[0055] (1) Add 2 L of saturated lithium carbonate solution to the reactor, heat to 90°C, add lithium carbonate seed crystals, the amount of which is 5% of the mass of lithium carbonate in the lithium bicarbonate solution, and stir evenly.

[0056] (2) Take a total volume of 30 L of lithium bicarbonate solution and add it at a dropping rate of 100 mL / min.

[0057] (3) During the first 5 L feeding process (i.e. the first 1 / 6 material feeding stage), ultrasonic treatment is turned on with an ultrasonic frequency of 28 kHz and a power of 350 W; during the remaining 25 L feeding process, ultrasonic treatment is turned off.

[0058] (4) After the addition is complete, continue stirring at a stirring rate of 300 rpm for 60 min. Then, the reaction slurry is separated into solid and liquid. The filter cake is washed twice with high-temperature pure water and dried under vacuum at 110°C for 6 h to obtain lithium carbonate product.

[0059] Product testing: The lithium carbonate product was measured using a laser particle size analyzer, with D10 = 5.303 μm, D50 = 15.750 μm, and D90 = 32.840 μm. ICP-OES analysis showed the results in Table 4, with a purity of 99.992%. The shorter sonication time in the first 1 / 6 of the time resulted in fewer crystal nuclei, allowing for a relatively sufficient solute supply in the subsequent stages, enabling each nucleus to grow into a large particle. However, compared to Example 1, where the sonication time was extended to the first 1 / 3, more crystal nuclei were generated, consuming more solute and limiting subsequent growth space, thus inhibiting particle growth. Simultaneously, the presence of numerous small particles lowered the overall average particle size; therefore, the average particle size at 1 / 6 of the sonication time was slightly higher than at 1 / 3 of the sonication time.

[0060] Table 4. Composition content of the lithium carbonate product prepared in Example 2

[0061]

[0062] Example 3

[0063] This embodiment 3 is basically the same as the embodiment, except that the frequency of the ultrasound is 28 kHz and the power is 200W.

[0064] Product testing: The lithium carbonate product was measured using a laser particle size analyzer, and the particle sizes were D10 = 4.483 μm, D50 = 12.864 μm, and D90 = 26.293 μm. ICP-OES analysis showed the results, as shown in Table 5, indicating a purity of 99.991%.

[0065] Table 5. Composition content of the lithium carbonate product prepared in Example 3

[0066]

[0067] Comparative Example 1

[0068] The raw materials for Comparative Example 1 are the same as those for Example 1, except that high-purity lithium carbonate is prepared using a traditional carbonization pyrolysis method, specifically including the following steps:

[0069] A reactor containing the same volume of lithium bicarbonate solution as in Example 1 was directly heated to 90°C and pyrolyzed for 2 hours with a stirring speed of 500 rpm. After the reaction, the lithium carbonate product was obtained through solid-liquid separation, washing, and drying.

[0070] Product testing: The lithium carbonate product was measured using a laser particle size analyzer, and the particle sizes were D10 = 17.929 μm, D50 = 50.975 μm, and D90 = 121.269 μm. ICP-OES analysis showed the results, as shown in Table 6, indicating a purity of only 99.17%.

[0071] Table 6. Composition content of lithium carbonate products prepared in Comparative Example 1

[0072]

[0073] Comparative Example 2

[0074] Comparative Example 2 is essentially the same as Example 1, except that water is used as the substrate. Specifically, it includes the following steps:

[0075] (1) Add 2 L of deionized water to the reactor, heat to 90°C, add lithium carbonate seed crystals, the amount of which is 5% of the theoretical lithium carbonate content in the lithium bicarbonate solution, and stir evenly.

[0076] (2) Take a total volume of 30 L of lithium bicarbonate solution and add it continuously to the reactor using a peristaltic pump at a dropping rate of 100 mL / min.

[0077] (3) During the first 10 L feeding process (i.e. the first 1 / 3 material feeding stage), ultrasonic treatment is turned on with an ultrasonic frequency of 28 kHz and a power of 350 W; during the remaining 20 L feeding process, ultrasonic treatment is turned off.

[0078] (4) After the addition is complete, continue stirring at a stirring rate of 300 rpm for 60 min. Then, the reaction slurry is separated into solid and liquid. The filter cake is washed twice with high-temperature pure water and dried under vacuum at 110°C for 6 h to obtain lithium carbonate product.

[0079] Product testing: The lithium carbonate product was measured using a laser particle size analyzer, and the particle sizes were D10 = 2.278 μm, D50 = 8.005 μm, and D90 = 18.752 μm. ICP-OES analysis showed the results, as shown in Table 7, indicating a purity of 99.90%.

[0080] Table 7. Composition content of lithium carbonate products prepared in Comparative Example 2

[0081]

[0082] Comparative Example 3

[0083] Comparative Example 3 is basically the same as Example 1, except that the ultrasonic time period is during the first 15 L of feeding process (i.e., the first 1 / 2 material feeding stage).

[0084] Product testing: The lithium carbonate product was measured using a laser particle size analyzer, and the particle sizes were D10 = 1.807 μm, D50 = 7.214 μm, and D90 = 16.672 μm. ICP-OES analysis showed the results, as shown in Table 8, with a purity of 99.994%. The tap density was 1.07 g / cm³.

[0085] Table 8. Composition content of lithium carbonate products prepared in Comparative Example 3

[0086]

[0087] Comparative Example 4

[0088] Comparative Example 4 is essentially the same as Example 1, except that ultrasound is not used throughout the entire process. The specific steps are as follows:

[0089] (1) Add 2 L of saturated lithium carbonate solution to the reactor, heat to 90°C, add lithium carbonate seed crystals, the amount of which is 5% of the theoretical lithium carbonate content in the lithium bicarbonate solution, and stir evenly.

[0090] (2) Take a total volume of 30 L of lithium bicarbonate solution and add it continuously to the reactor using a peristaltic pump at a dropping rate of 100 mL / min.

[0091] (3) After the addition is complete, continue stirring at a stirring rate of 300 rpm for 60 min. Then, the reaction slurry is separated into solid and liquid. The filter cake is washed twice with high temperature pure water and dried under vacuum at 110℃ for 6 h to obtain lithium carbonate product.

[0092] Product testing: The lithium carbonate product was measured using a laser particle size analyzer, and the particle sizes were D10 = 4.942 μm, D50 = 11.123 μm, and D90 = 33.808 μm. ICP-OES analysis showed the results, as shown in Table 9, indicating a purity of 99.987%.

[0093] Table 9. Composition content of lithium carbonate products prepared in Comparative Example 4

[0094]

[0095] Furthermore, particle size analysis was performed on the lithium carbonate products prepared in the embodiments and comparative examples of this invention, and the results are as follows. Figures 2 to 7 , Figure 9 As shown in the figure, the lithium carbonate products corresponding to Examples 1 to 3 exhibit a distinct bimodal characteristic. In contrast, the lithium carbonate products prepared in Comparative Examples 1 to 4 show a broad distribution and no bimodal structure. Furthermore, the morphological characterization of the lithium carbonate products prepared in Examples 1 and 4 was performed simultaneously, and the results are shown below. Figure 1 and Figure 8 As shown. By Figure 1 It can be seen that the product crystals prepared in the embodiments of the present invention have a rod-like morphology. And... Figure 8 The lithium carbonate product of Comparative Example 4 shown exhibits an irregular blocky and partially flake-like morphology.

[0096] base Based on the above experimental results, further comparison with Examples 1 and Comparative Example 1 shows that the lithium carbonate product prepared by the method of the present invention, compared with the traditional direct carbonation pyrolysis method, exhibits a distinct bimodal particle size characteristic, resulting in a tap density of 1.20 g / cm³ or higher. Simultaneously, the purity can reach over 99.9%. Furthermore, it achieves a rod-like morphology, fundamentally avoiding the formation of needle-like or plate-like morphologies that are detrimental to dense packing. In contrast, the lithium carbonate product prepared by the traditional direct carbonation pyrolysis method, when tested for purity by titration, shows a lower purity than the incoming material. This verifies that in the lithium carbonate product prepared by direct carbonation pyrolysis, undecomposed lithium bicarbonate is encapsulated within the lithium carbonate crystals, leading to low purity.

[0097] Comparing Example 1 and Comparative Example 2, using a saturated lithium carbonate solution as the substrate resulted in a distinct bimodal structure. However, using pure water as the substrate resulted in a disordered multimodal structure. Based on these results, the mechanism analysis reveals that, firstly, the use of a saturated lithium carbonate solution as the substrate allows the lithium carbonate produced by the added lithium bicarbonate to instantly convert into effective supersaturation. Combined with the preceding ultrasonic cavitation, this immediately and instantaneously generates a large number of uniform secondary crystal nuclei, eliminating the concentration buffer period and shaping the small-diameter peaks in the bimodal distribution. Furthermore, compared to a pure water system, the saturated lithium carbonate solution has a buffering capacity, effectively mitigating the differences in crystal nucleation rate caused by fluctuations in local pH or concentration due to carbon dioxide produced by the pyrolysis of lithium bicarbonate, thereby preventing the formation of multimodal, disordered aggregates.

[0098] Based on the explosive primary nucleation in the front stage, the subsequent stage uses non-ultrasonic operation. The lithium carbonate generated by the pyrolysis of lithium bicarbonate continues to grow epitaxially along the lithium carbonate seed crystals with their own particle size base and the lithium carbonate nuclei formed by the primary nucleation under suitable low supersaturation conditions, eventually forming a bimodal structure of large particles + small particles.

[0099] Comparing Example 1 and Comparative Example 3, it can be seen that if the ultrasonic time is too long, the continuous high supersaturation inhibits crystal growth, and the overall particles become finer and have no bimodal distribution.

[0100] Comparing Example 1 and Comparative Example 4, it is evident that without ultrasound, pyrolysis crystallization relies on natural nucleation, resulting in a low and uncontrollable nucleation rate. Crystal formation is primarily heterogeneous nucleation, leading to a long growth time and the tendency for particles to develop into irregular blocks and plates. Due to the lack of fine nuclei, although the particle size distribution is wide (D90 = 33.81 μm), the D10 is relatively large (4.94 μm), preventing small particles from effectively filling the gaps between larger particles, resulting in a packing density of only 1.04 g / cm³. Furthermore, the slow growth allows impurities to enter the crystal lattice, resulting in slightly lower purity.

Claims

1. A method for preparing high-purity lithium carbonate with a bimodal particle size distribution, characterized in that, Includes the following steps: (1) Using a saturated lithium carbonate solution as the base liquid, heat it to 90-95℃ and add lithium carbonate seed crystals; (2) Add the carbonized lithium bicarbonate solution to the bottom liquid in step (1) by dripping. During the first 1 / 6-1 / 3 of the feeding volume of the lithium bicarbonate solution, turn on the ultrasonic treatment. During the feeding of the remaining material, turn off the ultrasonic treatment. After the feeding is completed, stir the reaction, separate the solid and liquid, wash and dry to obtain high-purity lithium carbonate with bimodal particle size distribution.

2. The method for preparing high-purity lithium carbonate with a bimodal particle size distribution according to claim 1, characterized in that, The volume ratio of the lithium bicarbonate solution to the saturated lithium carbonate solution is (10-25):

1.

3. The method for preparing high-purity lithium carbonate with a bimodal particle size distribution according to claim 1, characterized in that, In step (1), the amount of lithium carbonate seed crystals added is 2%-10% of the mass of lithium carbonate in the lithium bicarbonate solution.

4. The method for preparing high-purity lithium carbonate with a bimodal particle size distribution according to claim 1, characterized in that, In step (2), the dripping rate is 50-100 mL / min.

5. The method for preparing high-purity lithium carbonate with a bimodal particle size distribution according to claim 1, characterized in that, In step (2), the ultrasonic frequency of the ultrasonic treatment is 24-40kHz and the ultrasonic power is 200-500W.

6. The method for preparing high-purity lithium carbonate with a bimodal particle size distribution according to claim 1, characterized in that, In step (2), the stirring reaction time is 30-150 min and the stirring rate is 200-500 rpm.

7. The method for preparing high-purity lithium carbonate with a bimodal particle size distribution according to claim 1, characterized in that, In step (2), the drying is performed under vacuum at 100-120°C for 4-8 hours.